Evaluation of DHF Surveillance System in District Blora 2017 - ahmad musyafa (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Background: In the last 49 years, dengue has emerged as a major health problem in Indonesia. Prevention and control of endemic diseases is done by improving surveillance system. Objective: Evaluation of DHF surveillance system in District of Blora 2017 Method: Descriptive observational study in the form of evaluation. The subjects were 26 DHF surveillance officers at public health center and 2 surveillance officers of Blora District Health Office. Data were collected by interview and observation. Result: surveillance system in PHC and hospital identify cases with clinical case report so that sensitivity is needed for early detection. The case definition has high sensitivity. All health centers have followed the guidelines from the Ministry of Health and WHO but the cases are found only as a suspect due to laboratory examination only thrombocyte and hematocrit, can not be analyzed trends of events either graph (weekly, monthly, yearly) minimal and minimum time series pattern. During 2016 in Blora District 713 reported cases of dengue with CFR 1.26. Availability of DHF guidebook (65.38%), nurse 53.85%, 0% healthiness. Of the 26 PHC, 65.38% of the surveillance personnel have never had training with 100% having double duty. Ability to process and analyze data below 40%, accuracy and completeness of report below 60% (Ewars) and 42% (STP). The immediate response has been made by the health department but not yet at the puskesmas level because the DHF report is still awaiting information from the active surveillance of the health department at the hospital in Blora. Discussion: This study emphasizes the need for laboratory-based dengue surveillance systems especialli trained personnel. Education and training is a supporting factor in improving DHF surveillance system especially in processing, analyzing and presenting data for guidance in making policy in Blora Regency.